EFFECTIVENESS OF BIO-INVIGORATION TECHNIQUE AGAINST VIABILITY AND VIGOR OF SOME COCOA SEED SOURCE - Fitrianti Handayani; La Ode Safuan; Gusti Ayu Kadek Sutariati (Universitas Sembilanbelas November Kolaka, 2016)
The research was aimed to evaluate the effectiveness of bio-invigoration treatment and seed sources on seed viability and vigor. The experiment was conducted in Agronomy Laboratory Unit of Agriculture Faculty of Haluoleo University, from January to May 2013. Laboratory research was arranged in split plot completely design. The main factor was variety which consisted of 3 varieties i.e. Hybrid (V1), Sulawesi 1 (V2) and Sulawesi 2 (V3). The sub plot was seed bio-osmoconditioning with rhizobacteria treatments which consisted of 6 treatments, namely: without seed bio-osmoconditioning (B0), seed bio-osmoconditioning with Bacillus sp. CKD061 (B1), seed bio-osmoconditioning with P. fluorescens PG01 (B2), seed bio-osmoconditioning with S. liquefaciens SG01 (B3), seed bio-osmoconditioning with Trichoderma sp. (B4), and seed osmoconditioning with KNO3 (B5). Every treatment was replicated 3 times. Therefore, overall there were 54 experimental units. Data obtained were analized using analysis of variance and followed with Duncan’s Multiple Range Test. The result of experiment in the Laboratory showed that Bacillus sp. CKD061 and Trichoderma sp. were efective in improving viability and vigor of all seed sources of cocoa seed used. In all seed sources used (Hybrid, Sulawesi 1, and Sulawesi 2), these treatment were effective in increasing germination power, homogenous growth, index vigor, and growth compared with untreated treatment. For the best result, still needed further research to evaluated stability effect of seed bio-osmoconditioning on cocoa seedling in the field